Aquaculture impact and treatment systems of effluents with aquatic macrophytes - Henry-Silva, G G; Camargo, AFM (Boletim do Instituto de Pesca, 2008)
Aquaculture effluents are enriched by nitrogen, phosphorus and organic matter and contribute to increase eutrophication of the receiving water bodies and reduction or change in biodiversity. To reduce effluent loading is important to formulate highly digestible diets with lower nutrient levels. In addition, it is necessary to treat effluents to attend to new legislation demands and the pressure of environmentalist. This review of the aquaculture activities and its impacts on the environmental is divided into fourth main subjects. The first is the way in which aquaculture affects the environmental through the consumption of materials and energy. The second is how aquaculture can affect the environmental directly, particularly through the effluents. The third is on the systems for treatment of aquaculture effluents with aquatic macrophytes. The fourth part is how aquaculture can be developed of sustainable form is on the systems for treatment of aquaculture effluents with aquatic macrophytes.